URGENSI PEMANFAATAN RUANG KAWASAN PERMUKIMAN BERDASARKAN RENCANA DETAIL TATA RUANG DI KABU-PATEN BANGGAI - Nur Alam Kahohon (Universitas Tadulako, 2025)
The purpose of this research is to find out the urgency of spatial utilization of settlement areas and detailed spatial plans in Banggai Regency, and to find out the utilization of detailed spatial plans based on the principles of sustainable development. The research method uses normative legal research, using statutory approaches, conceptual approaches, and case approaches. The Spatial Detail Plan is regulated in several existing regulations including Law Number 26 of 2007 concerning Spatial Planning which regulates the detailed spatial plan as an operationalization of the RUTR and in its instrument the RDTR is used as the basis for the preparation of zoning regulations, as well as in Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation which confirms that Local Governments are required to compile RDTR in digital form and according to standards to enable the public to access it. Tujuan penelitian ini Untuk Mengetahui urgensi pemanfaatan ruang kawasan permukiman dan rencana detail tata ruang di Kabupaten Banggai, dan Untuk mengetahui pemanfaatan rencana detail tata ruang berdasarkan prinsip-prinsip pembangunan berkelanjutan. Metode penelitan menggunakan Penelitian hukum normatif, dengan menggunakan pendekatan perundang-undangan, pendekatan konsep, dan pendekatan kasus. Rencana Detail Tata Ruang yang di atur dalam beberapa aturan yang ada meliputi Undang-Undang Nomor 26 Tahun 2007 Tentang Penataan Ruang yang menagtur tentang rencana rinci tata ruang sebagai oprasionalisasi RUTR dan dalam instrumennya RDTR digunakan sebagai dasar bagi penyusuan peraturan zonasi, serta dalam Peraturan Pemerintah Pengganti Undang-Undang Nomor 2 Tahun 2022 Tentang Cipta Kerja yang menegaskan bahwa Pemerintah Daerah wajib menyusun RDTR dalam bentuk digital dan sesuai standar untuk memudahkan masyakat mengaksesnya.